Ultrafast, Self-Driven, and Air-Stable Photodetectors Based on Multilayer PtSe2/Perovskite Heterojunctions - Zhang, Zhi-Xiang; Long-Hui Zeng; Tong, Xiao-Wei; Gao, Yang; Xie, Chao; Tsang, Yuen Hong; Luo, Lin-Bao; Wu, Yu-Cheng (The journal of physical chemistry letters, 2018)
We report on the large-scale synthesis of polycrystalline multilayer PtSe2 film with typical semimetallic characteristics. With the availability of the large-area film, we constructed a heterojunction composed of multilayer PtSe2 and Cs-doped FAPbI3, which can function as a self-driven photodetector in a broadband wavelength from the ultraviolet to the near-infrared region. Further photoresponse analysis revealed that the heterojunction device showed outstanding photosensitive characteristics with a large I light/I dark ratio of 5.7 × 103, high responsivity of 117.7 mA W–1, and decent specific detectivity of 2.91 × 1012 Jones at zero bias. More importantly, the rise/fall times were estimated to be 78/60 ns, rendering our device the fastest device among perovskite-2D photodetectors reported to date. In addition, it was also observed that the PtSe2/perovskite photodetector can almost retain its photoresponse properties after storage in ambient conditions for 3 weeks. This study suggests the potential of the present PtSe2/perovskite heterojunction for future air-stable ultrafast photodetecting applications.